Inhibition of TGF-β/Smad3 Signaling Disrupts Cardiomyocyte Cell Cycle Progression and Epithelial–Mesenchymal Transition-Like Response During Ventricle Regeneration - Peng, Yuanyuan; Wang, Wenyuan; Fang, Yunzheng; Hu, Haichen; Chang, Nannan; Pang, Meijun; Hu, Ye-Fan; Li, Xueyu; Long, Han; Xiong, Jing-Wei; Zhang, Ruilin (Frontiers in Cell and Developmental Biology, 2021)
Unlike mammals, zebrafish can regenerate injured hearts even in the adult stage. Cardiac regeneration requires the coordination of cardiomyocyte proliferation and migration. The TGF-β/Smad3 signaling pathway has been implicated in cardiac regeneration, but the molecular mechanisms by which this pathway regulates cardiomyocyte proliferation and migration have not been fully illustrated. Here, we investigated the function of TGF-β/Smad3 signaling in a zebrafish model of ventricular ablation. Multiple components of this pathway were upregulated/activated after injury. Utilizing a specific inhibitor of Smad3, we detected an increased ratio of unrecovered hearts. Transcriptomic analysis suggested that the TGF-β/Smad3 signaling pathway could affect cardiomyocyte proliferation and migration. Further analysis demonstrated that the cardiomyocyte cell cycle was disrupted and the epithelial-mesenchymal transition (EMT)-like response was impaired, which limited cardiac regeneration. Altogether, our study reveals an important function of TGF-β/Smad3 signaling in cardiomyocyte cell cycle progression and EMT process during zebrafish ventricle regeneration.